Hypohidrotic Ectodermal Dysplasia: Prosthetic Rehabilitation of a Rare Pediatric Case - Monalisa Das; Mrinmay Aulia (Journal of Primary Care Dentistry and Oral Health)
Prosthetic management of hypohidrotic ectodermal dysplasia can be considered an early intervention for an affected child, not only to optimize esthetics and the functioning of the stomatognathic system but also to improve general nutrition and health. Removable prostheses with periodic modifications are a wise treatment choice for a developing child. This case report highlights the need for early detection and oral management of an 8-year-old male child with this rare condition.